Influence of Retained Fetal Membranes on Reproductive Health of Crossbred Cows - Rokde, K.; Kumar, S.; Mahour, S.S.; Nema, S.P.; Aich, R.; Bhardwaz , A. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
A study was carried out to compare the effect of retained fetal membranes on reproductive health of crossbred cows. 24 crossbred cows selected were divided into control group (consisted of 6 cows which had normal 3rd phase of parturition) and RFM group (consisted of total 18 cows with retained fetal membranes for more than 12 hrs). The time required for expulsion fetal membranes, cessation of lochial discharge, gross uterine involution, service period and number of AI required per conception was significantly (P<0.05) higher and appearance of first postpartum estrus was non significantly higher in retained fetal membranes (RFM) cows than normally calved cows.